Factors affecting farmer demand and pour-on treatments in Ethiopia - Wangila, J.; Swallow, B.M.; Tesfamichael, N.; Okello, O.; Kruska, Russell L. (OAU/STRC, 1999)
Animal trypanosomosis is particularly important in Ethipia where 7-10 million cattle are at risk. A geo-referenced census of over 5000 households was conducted between March and July 1996 to better understand factors affecting demand of the a cypermethrin pour-ons used since January 1991 to control tsetse in Ghibe, Ethiopia. Since December 1992, farmers have paid 3 Ethiopian Birr (US$0.50) for each pour-on treatment offered once a month at 9 supply centres. Geographic Information Systems (GIS) and econometrics were used to identify and quantify effects of different economic, demographic and spatial factors on farmer demand for the pour-ons. Results show that household-level demand for the pour-on depends upon season, characteristics of the household head, structure of the cattle herd, distance to the nearest supply point and characteristics of the household's neighbours. Demand is highest in the wet season and lowest in the dry season. Female-headed households were more likely to treat their cattle than male-headed households, while households located farther from the treatment centres were less likely to treat. Households whose neighbours treated a large number of animals were more likely to treat, while households, with a large number of cattle-owning neighbours were less likely to treat. These results suggest that there is a type of informal collective action occurring supported by peoples' observation of their neighbours' behaviour.